RAZALI ISMAIL URGES GRADUATES TO BE THANKFUL, APPRECIATIVE AND ALWAYS SAFEGUARD INTEGRITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, November 2015 – In view of the unsettling events occurring all over the world, the graduates of today need to be thankful and appreciative of all that they have received as there are many others being deprived of opportunities for education the world over and are facing struggles in their daily lives.